The Relationship Between Stress Levels and Self-Care Management in Elderly Individuals with Hypertension - Ni Putu Natari Ayunda Oktavia; Irwina Angelia Silvanasari; M. Elyas Arif Budiman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
Elderly individuals undergo gradual physical and psychological deterioration. They commonly encounter difficulties in self-care management, potentially exacerbating their health conditions. Self-care management among elderly individuals with hypertension tends to be inadequate. Challenges within self-care management among the elderly often stem from stress. The objective of this study is to analyze the relationship between stress levels and self-care management among elderly individuals with hypertension. This research employs a quantitative design with a cross-sectional correlation approach. The sample in this study consists of 145 elderly individuals with hypertension, selected using cluster random sampling. The study utilizes the Hypertension Self-Management Behavior Questionnaire (HSMBQ) and the Perceived Stress Scale (PSS). The results, analyzed using the gamma test, show a contingency coefficient P-value of -0.991 and a P-value of 0.000 ≤ 0.05. Statistically, this indicates a significant relationship between stress levels and self-care management, with a very strong negative correlation. This means that lower stress levels are associated with better self-care management. Elderly individuals experiencing high stress are unable to effectively manage self-care, highlighting the need for optimal individualized stress management to improve the health status of the elderly.